Biomarkers of exposure to tobacco smoke and environmental pollutants in mothers and their transplacental transfer to the foetus. Part II. Oxidative damage - Rossner, P; Milcova, A; Libalova, H; Novakova, Z; Topinka, J; Balascak, I; Sram, R J (Mutation research, 2009)
Oxidative damage to macromolecules may have numerous negative health consequences. We measured oxidative damage to DNA, proteins and lipids in 80 newborns and 79 mothers, analyzed the effect of mother's tobacco smoke exposure on oxidative stress, and assessed correlations between oxidative stress markers and bulky and PAH (polycyclic aromatic hydrocarbons)-specific DNA adducts. Mean levels (+/-S.D.) of 8-oxodeoxyguanosine (8-oxodG) per 10(5) dG in the placenta were 2.85+/-0.78; we did not see a difference between 8-oxodG levels in newborns born to mothers exposed and unexposed to tobacco smoke. Protein carbonyl levels, a marker of protein oxidation, were comparable in the umbilical cord and in maternal venous blood plasma (17.4+/-3.2 and 17.6+/-4.2nmol/ml plasma in newborns and mothers, respectively, p=0.66). Lipid peroxidation measured as levels of 15-F(2t)-isoprostane (15-F(2t)-IsoP) in plasma was significantly higher in newborns than in mothers (362+/-129 and 252+/-130pg/ml in newborns and mothers, respectively, p<0.001). We did not find any effect of tobacco smoke exposure on either biomarker in any group. Levels of both protein carbonyls and 15-F(2t)-IsoP in cord blood significantly correlated with those in maternal plasma (p<0.001). 8-oxodG levels positively correlated with plasma carbonyls in cord plasma, as well as with cotinine levels (marker of tobacco smoke exposure) in maternal plasma. 8-oxodG levels also correlated with bulky DNA adducts in lymphocyte DNA of newborns and mothers and with PAH-DNA adducts in the placenta. Our results showed higher lipid peroxidation in newborns than in mothers, close correlation of analyzed oxidative stress markers between newborns and mothers, and a relationship between oxidative stress and induction of DNA adducts.
Keywords: polycyklické aromatické uhlovodíky; maternofetální výměna látek; Oxidative Stress; novorozenec; Infant, Newborn; oxidační stres; Maternal Exposure; Humans; Pregnancy; kotinin; Lymphocytes; lymfocyty; Deoxyguanosine; Vitamin E; Placenta; oxidace-redukce; F2-isoprostany; Female; mladý dospělý; dospělí; peroxidace lipidů; Protein Carbonylation; ELISA; Vitamin A; krevní proteiny; lidé; Biomarkers; Air Pollutants; Polycyclic Aromatic Hydrocarbons; karbonylace proteinů; Enzyme-Linked Immunosorbent Assay; Fetal Blood; F2-Isoprostanes; látky znečišťující vzduch; Adult; Blood Proteins; vitamin A; 8-Hydroxy-2'-Deoxyguanosine; biologické markery; ženské pohlaví; fetální krev; Cotinine; deoxyguanosin; těhotenství; Oxidation-Reduction; Young Adult; 8-hydroxy-2'-deoxyguanosin; Smoking; Maternal-Fetal Exchange; matka - expozice noxám; placenta; kouření; adukty DNA; vitamin E; DNA Adducts; Lipid Peroxidation